2021
DOI: 10.1108/cg-08-2020-0357
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance practices and the pandemic crisis: UK evidence

Abstract: Purpose This paper aims to investigate the impact of the COVID-19 pandemic on the corporate governance practices in the UK. The authors adopt a case study approach and use content analysis, using internal and external media releases as well as annual reports to analyse the impact of the pandemic on governance practices. Design/methodology/approach The research design is qualitative in nature and adopts a case study approach. HSBC, an international bank, is used as the case study and a content analysis of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The 2008 global financial crisis had a tremendous impact on financial institutions and businesses (Sivaprasad and Mathew, 2021). However, the enterprise world is expected to have drastic outcomes because of coronavirus crisis on physical, emotional, fitness and commercial enterprise aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The 2008 global financial crisis had a tremendous impact on financial institutions and businesses (Sivaprasad and Mathew, 2021). However, the enterprise world is expected to have drastic outcomes because of coronavirus crisis on physical, emotional, fitness and commercial enterprise aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Ullah [4] predicted possible financial distress and corporate defaults in Pakistan as a post COVID 19 review and found an increase in the degree of financial distress upon which they based their prediction as well as a likely increase in the number of corporate failures due to poor governance. Sivaprasad and Mathew [15] investigated the COVID -19 pandemic's impact on corporate governance in the United Kingdom (UK) and their findings revealed that many firms lag in IT-related risk control as an alternative to governance during the pandemic. The authors suggested that firms should address the adequacy of IT governance as a matter of urgency which can cater for potential future risks that nature may bring.…”
Section: Prior Studies On the Covid -19 Pandemic Corporate Governance...mentioning
confidence: 99%
“…Corporate governance ensures effective communications with the stakeholders, effectiveness and efficiency, well managed risks, goal achievement and compliance through transparency and accountability [6]. In addition, for companies that want to be resilient and sustainable, Sivaprasad and Mathew [15] state that IT governance and other sustainable good governance such as good management of staff through remunerations and other welfare programs must be held. There are many reasons for ensuring good corporate governance in companies.…”
Section: Introductionmentioning
confidence: 99%
“…Future research opportunities are summarized as follows: COVID-19 pandemic and corporate governance practices : The COVID-19 pandemic is a hot and recent topic to consider when adjusting corporate governance practices. Sivaprasad and Mathew (2021) and Le and Nguyen (2022) have considered the impact of COVID-19 on corporate governance practices in Vietnam and the UK, respectively. There is a need to further understand how this pandemic has affected corporate governance across countries and industries, including financial and nonfinancial companies.…”
Section: Directions For Future Corporate Governance Research Topicsmentioning
confidence: 99%
“…In addition, several other studies have investigated the possible associations of corporate governance with different corporate decisions, such as capital structure (Sheikh and Wang, 2012), investment efficiency (Ullah et al , 2020), earnings management (Wan Mohammad et al , 2016) and dividend policy (Sanan, 2019). Recently, a few studies have considered recent trends in financial markets, such as blockchain technology (Singh et al , 2020) and the COVID-19 pandemic (Sivaprasad and Mathew, 2021). Through bibliometric analysis, this study determined the most frequent corporate governance research topics and identified various avenues for future research.…”
Section: Introductionmentioning
confidence: 99%